The Capital Structure Of Malaysian Firms In The Aftermath Of Asian Financial Crisis 1997 - Liew, Lewis Teo Piaw; Mohamad, Jais (EBSCO, 2014)
The Asian Financial Crisis 1997 had revealed the issues of excessive leverage that caused the firms in Malaysia for being vulnerable to the economic turmoil. Hence, capital structuring and particularly the establishment of the contingent capital structure have been the central concern. Grounded on the contingency theory and the traditional capital structure theories, this study intends to identify what constitutes organizational-environmental fit to the contingent capital structure in Malaysia and how fast they had adjusted towards their contingent capital structure in the aftermath of the crisis. The findings reveal that while Malaysia has successfully sustained the firms’ leverage to a lower level, it was not so successful to ensure speedy adjustment given its rigorous institutional settings and also access to financial and capital market. A better understanding of the contingent capital structure formulation and adjustment process via fresh empirical evidence do not only provide insights to the practitioners into the adaptation strategy but also have important implications for the design and implementation of the financial reforms in addressing future crisis.